Tachycardia – induced cardiomyopathy (TIC): a reversible state - Jovanova, Silvana; Arnaudova-Dezhulovikj, F; Kostova, Nela; Poposka, Lidija; Kedev, Sashko (Hrvatsko kardiološko društvo, 2012)
Tachycardia-induced cardiomyopathy (TIC) is defined as a condition characterized by atrial or ventricular myocardial dysfunction as a result of prolonged and increased atrial or ventricular rates. There is no underlying structural heart disease, and the condition is reversible upon control of the arrhythmia. The prevalence of the disease can’t be truly estimated as it is mainly described in case reports. During 2011 we established the diagnosis of tachycardia induced cardiomyopathy in 4 patients. All of them were male, at the age of 40–55, with no previous cardiovascular disease. At the time of presentation two patients had atrial fibrillation, and the other two of them atrial flutter, with fast ventricular rate (130–160 bpm. All of them presented with symptoms and signs of congestive heart failure. The duration of the arrhythmias was approximately 4–8 weeks before hospitalization. On admission, echocardiographic parameters were consistent with dilated cardiomyopathy with moderately to severe reduced ejection fraction (25–40%). In all cases there was no structural heart disease, no signs of inflammation or metabolic disturbances. Coronary angiography showed normal coronary arteries. In all cases there was resolution of the ventricular dysfunction following appropriate treatment of the arrhythmias and achieving and maintaining sinus rhythm. During the follow-up period of 12–18 months the patients are in NYHA I functional class, with echocardiographic dimensions and volumes within normal ranges, on beta blockers, ACE inhibitors, ASA or OAT. Two of them had few episodes of AF of short duration. The recognition of tachycardia-induced cardiomyopathy is important as appropriate treatment (rhythm and/or rate control) has a good outcome. It needs to be taken into consideration in the differential diagnosis of idiopathic dilated cardiomyopathy.
Keywords: tachycardia-induced